Antioxidant and Antibacterial Activities of Dried and Effervescent of Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) - W., Tri Dewanti; Wulan, Siti Narsitoh; C., Indira Nur (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The research was conducted to compare antioxidant and antibacterial activities of some products derived from a typical fruit, locally known as Mahkota Dewa fruit (Phaleria macrocarpa (Scheff) Boerl). These products consist of: a dried fruit, an instant powder (produced by high temperature processing technique) and effervescent powder (produced by low temperature processing technique). The antioxidant activity was monitored within 8 days incubation, and the activity was determined after 24 hours of incubation against two respective bacteria, namely Staphylococcus aureus and Eschericia coli at various concentrations i.e.: 12.5%; 25% and 50%Â respectively. The results showed that the three products contain high levels of antioxidant, but were less stable than that of the synthetic one. The highest antioxidant activity of all product was identified on the 4th day of incubation: 48,71% (an effervescent powder); 37,88% for the dried fruit and 33,27% for instant powder) the antioxidant activity of fruit and fruit product dropped significantly after 4 days of incubation. The products were more effective against E. coli than S. aureus and the activity increases with concentration. Â Key Words: Mahkota Dewa, Antioksidant activity